Study on spinal anesthesia drugs used in Misurata hospitals for the year 2022 (Journal of Humanitarian and Applied Sciences, 2023)
Introduction: Spinal anesthesia is commonly used for procedures such as cesarean sections, lower limb surgeries, and certain urological procedures. The onset of action is rapid, and the duration of anesthesia is relatively shorter compared to general anesthesia. There are many medications that are used in spinal anesthesia, the most important of which are: Lidocaine, Bupivacaine, Lidocaine, Tetracaine, Mepivacaine, Ropivacaine, Levobupivacaine, and Chloroprocaine. Aims of study: The purpose of the present study is to discover the most common spinal anesthetics used in surgical operations by anesthesiologists in Misurata hospitals. Methodology: There were total of 48 anesthesiologists.  The respondents have worked in different hospitals in Misurata (public and private hospitals). Questionnaires were distributed to anesthesiologists in 2022. Results: The results show us that the largest number of the target audience had years of experience from (6-10) years, with a percentage of (35.4%). In addition, the vast majority of the targets were working in both the public and private sectors, where their percentage was (78.7%). In view of the results collected through a random sample of anesthesiologists inside Misurata hospitals, we note that most doctors use heavy morcaine as the first choice in regional anesthesia, where the percentage reached (52.4%), while other drug  was added to it as a second choice, with a percentage of (33.3%). In addition, one of the most important reasons that determines the choice of medicine in migraine is the type of surgery and the method of giving the medicine, while one of the most important reasons for adding another drug to heavy morcaine is to reduce the side effects or complications of this medicine and make it safer.
Keywords: Spinal Anesthesia; Misurata Hospitals